Uniform Strain-Dependent Thermal Conductivity of Pentagonal and Hexagonal Silicene - Liu, Huake; Qin, Guangzhao; Hu, Ming (Frontiers in Materials, 2021)
Two-dimensional (2D) pentagonal monolayer structures have shown promising characteristics and fascinating physical and chemical properties. The disparate strain-dependent thermal conductivity of two-dimensional penta-structures was reported, but the difference between the silicon-based pentagonal and hexagonal structures is barely researched. In this work, based on first-principles calculations, we studied the strain-modulated phonon transport behavior of two 2D pentagonal (penta-SiH and bilayer penta-Si) and one hexagonal silicene structures (H-silicene), of which the penta-SiH and H-silicene mean the structures are hydrogenated for the purpose of thermodynamical stability. We found that the silicon-based pentagonal structure also presented a different strain-dependent thermal conductivity from other pentagonal materials, such as penta-graphene, penta-SiC, or penta-SiN. Moreover, even with the similar strain-dependent thermal transport behavior in penta-SiH and bilayer penta-silicene, we find that the governing mechanism is still different. For both pentagonal silicene structures, the thermal conductivity presents a large improvement at first as the tensile strain increases from 0 to 10% and then stabilizes with a strain larger than 10%. A detailed analysis shows that the in-plane modes contributed the most part to the group velocity enhancement under strains in penta-SiH which is opposite from the bilayer penta-graphene, although the phonon group velocity and phonon lifetime of both structures increase with applied strain. On the other hand, a similarity was found in pentagonal silicene and hexagonal silicene despite the differences in geometry structures. Furthermore, based on the detailed analysis between the pentagonal (penta-SiH) and hexagonal silicene structures (H-silicene), the difference in out-of-plane phonon scattering cannot be ignored: different major scattering channels of the out-of-plane flexural modes result in different thermal conductivity sensitivity to strains, and the disparity in anharmonicity leads to different thermal conductivity under no strain.